CFD simulations of a Y-junction for the implementation of hydraulic short-circuit operating mode. Issue 1 (June 2021) - Decaix, J; Biner, D; Drommi, J-L.; Avellan, F; Münch-alligné, C
Abstract: In the framework of the XFLEX HYDRO H2020 European Project, one of the demonstrators focuses on the implementation of the hydraulic short-circuit on the pump storage power plant of Grand-Maison owned by Electricité De France (EDF). The Grand-Maison power plant is a two-level plant production with one plant located above the downstream reservoir and equipped with four Pelton turbines; a second plant located downstream the reservoir and equipped with eight reversible pump-turbines. Hydraulic short circuit consists in running pumps and turbines in the meantime to balance the energy consumption of the pumps compared to the grid. Such an operating mode allows increasing the flexibility of the power plant and targeting the requirement of balancing the intermittent production due to the growing of new renewable energies such as wind and solar power plants. The hydraulic short-circuit operating mode leads to a change in the flow paths in the penstocks and junctions compared to the normal turbine or pump modes. Indeed, compared to the pump mode, this mode will lead to a flow derivation at the junction between the penstocks directed to the Pelton units and the penstocks directed to the upper reservoir. As this mode have not been scheduled at the beginning of the power plant construction, it is necessary to quantitatively assess the singular head losses generated at the junction to be able to simulate the complete behaviour of the power plant by means of a 1D model. CFD simulations are carried out with the Fluent software for several configurations of hydraulic short-circuit defined by the ratio of flow rate deviated to the Pelton turbines.